Overexpression of regulatory T cells in patients with unexplained recurrent pregnancy loss: friend or foe? - Liu, Peng-cheng; Li, Jian-bin; Huang, Yi-ping; Zhang, Min; Yu, Shu-jiao; Wu, Rui (Frontiers in Medicine, 2024)
Background This study aimed to investigate the role of regulatory T cells in patients with unexplained recurrent pregnancy loss (URPL). Methods We retrospectively analyzed 136 women who had experienced two or more miscarriages before 24 weeks of gestation for no obvious reason from May 2018 to October 2021. The basic clinical data of the patients and expression of lymphocyte subsets such as regulatory T cells (Tregs) and natural killer cells (NKs) by flow cytometry were collected to explore the risk factors of pregnancy outcome in URPL patients. Results A total of 136 URPL patients were enrolled in this study. Eventually, 50 patients attained clinical pregnancy. The median age was 31.8 ± 4.6 years in patients with clinical pregnancy. The univariate and multivariate logistic regression analyses indicated that Tregs was associated with the pregnancy outcomes of patients with URPL (odds ratio 0.63, 95% confidence interval 0.50–0.80). More importantly, a U-shaped association was found between Tregs and pregnancy outcome (p < 0.001), with either higher or lower Tregs levels adversely affecting pregnancy outcome. Conclusion Tregs levels that are either too high or too low can harm pregnancy outcomes. It was expected to be a very promising quantitative biomarker for predicting pregnancy outcomes in URPL patients.